PEMETAAN RISET AKUNTANSI BERBASIS PENGUJIAN VARIABEL MOTIVASI - Ratih Rediyaningrum Putriaji; Imam Mas’ud (Universitas Jember, 2011)
Development of a discipline can not be separated from the role that research results are publicized in the literature and academic journals. A scientific discipline will not grow will die even if there is no research on the development of these disciplines. In the disciplines of accounting, accounting research has a very important role.First, accounting research role is to give effect to the accounting practices, so that accounting practices are not just from the road but it is based on research which is then developed in the theory. The theory that there would then be subject to empirical testing done in a sustainable manner. Thus, accounting research is not an end but it is the process for building theory and practice. The second role of accounting research is to improve understanding of environmental accounting to accounting practices are not understood as something taken for granted. Keywords : Motivation in Accounting for the development of accounting research.